Influence of micronutrients and manures on growth and yield of garlic (Allium sativum L.) in sandy loam soil - Mondal, Mohd Monjurul Alam; Akter, Md. Babul; Rahman, Md. Habibur; Puteh, Adam (Sciencedomain International, 2016)
Proper nutrient management is very important for increase yield of field crops in any type of soil. Field experiments were conducted under sub-tropical condition of Bangladesh for two consecutive years to study the response of garlic cv. Multiclove local to different combination of boron (B), zinc (Zn), cowdung (CD), chicken manure (CM) and mustard oil cake (OC) in the sandy loam soil. The treatments consisted of 12 combinations with B, Zn, CD, CM and OC. Application of boron had tremendous effect on growth and yield but Zn had no significant influence on growth and yield in garlic. OC added fertilizer combination showed the best performances regarding yield and yield attributes. CM added fertilizer combination had the second highest yield performance and showed non-significant difference with OC added fertilizer combination in garlic. Application of OC is not beneficial due to 30 times higher price than CD and CM. CM added fertilizer combination showed higher bulb yield with the higher economic return than CD added fertilizer combination. CM added fertilizer combination also had almost equal investment and cost-benefit ratio in comparison with CD. The lowest marginal benefit-cost ratio was observed in OC added fertilizer combination though it showed higher bulb yield as well as economic benefit. Based on marginal rate of return, the marginal farmers’ may be advised to follow NPKSB + CD fertilizer combination. The farmers having ability to invest more, may go to the treatment of NPKSBZn + CM or NPKSBZn + OC for maximum economic benefit and also sustainable soil health in sandy loam soil.